Evaluating ecological efficiency of voluntary conservation policy in boreal forest conservation - Jani Hohti; Anssi Lensu; Mikko Mönkkönen; Janne S. Kotiaho (Conservation Science and Practice)
Abstract There is a global call for more efficient voluntary conservation practices. Voluntary conservation requires landowner participation, which may limit conservation efficiency. Here, we evaluated the ecological costs and benefits of a voluntary conservation policy relative to obligatory conservation, two hypothetical scenarios of randomly distributed conservation area networks, and two hypothetical ecologically optimized conservation area networks. The study was based on spatial conservation prioritization maps reflecting the conservation priority of forest in Central Finland. Our results suggest that voluntary conservation area networks can be relatively cost‐efficient with higher nature values and better connectivity compared to a randomly selected conservation area network. Voluntary conservation area networks scored slightly higher nature values than the obligatory conservation area network but suffered from lower connectivity and smaller area size. Quality differences between the voluntary conservation area networks were minor. Our analysis showed that neither of the voluntary conservation area networks achieved its full conservation potential when compared to an ecologically optimized conservation area network. Thus, our results indicate that the societal pursuit of landowner's conservation acceptance, and hence rejection of the systematic conservation planning, has come with a cost of reduced nature values and connectivity in the current conservation area network.